2021
DOI: 10.3390/agronomy11030476
|View full text |Cite
|
Sign up to set email alerts
|

Apple Detection in Complex Scene Using the Improved YOLOv4 Model

Abstract: To enable the apple picking robot to quickly and accurately detect apples under the complex background in orchards, we propose an improved You Only Look Once version 4 (YOLOv4) model and data augmentation methods. Firstly, the crawler technology is utilized to collect pertinent apple images from the Internet for labeling. For the problem of insufficient image data caused by the random occlusion between leaves, in addition to traditional data augmentation techniques, a leaf illustration data augmentation method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The latest yolo series algorithm is Yolov5. Wu, Ma, Zhao, and Liu (2021) applied yolov4 to apple detection in complex environment. In this article, first, the data set is expanded by using data expansion algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…The latest yolo series algorithm is Yolov5. Wu, Ma, Zhao, and Liu (2021) applied yolov4 to apple detection in complex environment. In this article, first, the data set is expanded by using data expansion algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Their system had an AP of 96.28 % and a detection speed of 106 FPS on the high-powered Tesla V100 GPU. Other studies also evaluated the performance of YOLO-based models on detecting other fruits such as apple, lemon, banana and cherry [ 8 , 11 , 12 , 13 , 15 , 16 , 32 ].…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have utilized YOLO-based models for fruit detection and have demonstrated that YOLO models have a huge potential in accurate real time detection of fruits in an orchard [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, there were some concerns found among these studies.…”
Section: Introductionmentioning
confidence: 99%
“…e loss function remains the same as the YOLOv4 model, which consists of three parts: classification loss, regression loss, and confidence loss [28]. Classification loss and confidence loss remain the same as the YOLOv3 model, but complete intersection over union (CIoU) is used to replace mean-squared error (MSE) to optimize the regression loss [29].…”
Section: Vehicle Detection and Classificationmentioning
confidence: 99%